Wireless Radio Frequency Automation of Intelligent Optical Fiber Transmission System Based on the Differential Evolution Method - Lei Jin; Jinghong Zhao; Xing Huang; Bin Lu (Advances in Multimedia)
With the continuous development and improvement of science and technology, optical fiber transmission has been transformed from traditional manual transmission to automatic transmission, and the transmission efficiency is constantly improving. In order to further analyze the performance of the intelligent optical fiber transmission process, the differential evolution analysis method is introduced in this paper, integrated architecture is built through the integrated optical and intelligent optical fiber, and the corresponding vector signal error value is solved through the comparison of transmission schemes. The error value is about 9%, through simulation experiments, which can effectively meet the requirement of automation of the wireless radio frequency of the intelligent optical fiber transmission system and realize long-distance transmission.